Science, Technology, Engineering, and Mathematics (STEM) Project-based Learning to Enhance Students’ Multiliteracy on Renewable Energy: A Comparative Study between Urban and Rural Schools - Liandha Arieska Putri; Ida Kaniawati; Anna Permansari; Diana Rochintaniawati (Postgraduate, University of Mataram, 2026)
Early renewable energy education has become increasingly vital since the urgency of sustainability in the energy sector continues to grow. This study provided a comparative analysis of students’ multiliteracy enhancement between urban and rural schools in the Science, Technology, Engineering, and Mathematics Project-Based Learning (STEM-PjBL) setting. A quasi-experimental design was employed involving 120 students from one urban and one rural secondary school, selected using stratified random sampling. Multiliteracy was measured using pre- and post-tests and analyzed through normalized gain (N-gain) scores. Results indicated that both schools demonstrated moderate improvement in multiliteracy after the intervention. However, the urban school achieved relatively stronger performance compared with the rural school. It is found that urban students were associated with greater access to digital teaching and learning facilities. Conversely, rural students benefited from rich local knowledge and community practices related to natural resource management, which supported contextual understanding of renewable energy concepts. Future research is recommended to integrate sustainability education at earlier educational stages and further embed renewable energy applications within the formal curriculum to promote sustained multiliteracy development.